Pylera and sequential therapy for first-line Helicobacter pylori eradication: a culture-based study in real clinical practice. Issue 6 (June 2018) - Fiorini, Giulia; Zullo, Angelo; Saracino, Ilaria M.; Gatta, Luigi; Pavoni, Matteo; Vaira, Dino
Abstract : Background and aims: Italian guideline suggests 10-day sequential or bismuth-based quadruple therapies for first-line Helicobacter pylori treatment. Comparison between these regimens is lacking. We assessed the efficacy of these therapies in clinical practice and evaluated the role of primary bacterial resistance toward clarithromycin and metronidazole. Patients and methods: Consecutive patients with H. pylori infection were enrolled. Bacterial culture with antibiotics susceptibility testing was attempted in all cases. Patients received either a sequential therapy with esomeprazole 40 mg for 10 days plus amoxicillin 1000 mg for the first 5 days followed by clarithromycin 500 mg and tinidazole 500 mg (all twice daily) for the remaining 5 days, or bismuth-based therapy with esomeprazole 20 mg twice daily and Pylera 3 tablets four times daily for 10 days. H. pylori eradication was assessed by using 13 C-urea breath test. Results: A total of 495 patients were enrolled. Following sequential (250 patients) and quadruple (245 patients) therapies, the eradication rate were 92 and 91%, respectively, at intention-to-treat analysis and 96 and 97%, respectively, at per protocol analysis. Overall, the pattern of bacterial resistance did not significantly affect the cure rate, but the presence of clarithromycin and metronidazole dual resistance tended to reduce the success rate of both sequential (84.8 vs. 90.1%; P =0.4) and quadruple (85 vs. 94.1%; P =0.06) therapies. Adverse events occurred more frequently with the quadruple than with sequential therapy (56.9 vs. 25.8%; P <0.001). Conclusion: In our country, sequential and bismuth-based quadruple therapy achieved similarly high eradication rates as first-line treatments for H. pylori infection in clinical practice.